TINJAUAN TEOLOGIS TENTANG PEMBENTUKAN KARAKTER GURU PAK MENURUT DANIEL 6:1-29 - Holly Andrew Putranu Nino Faot; Nanik Sutarni; Pujiati Gultom (JURNAL PENABIBLOS, 2024)
This article discusses the example of Daniel 6:1-29 as a reference in forming the character of PAK teachers. This was written based on the existence of cases that show a true character crisis in the world of education, specifically regarding teachers. PAK teachers are part of teachers in general who are very relevant in character formation based on Daniel who is one of the Bible figures who has true character qualities and can be emulated. The aims of this research are: First, to explain character in accordance with Law No. 14 of 2005 which regulates the personality competence of a teacher. Second, to explain the character that is in accordance with the priority qualities of the PAK teacher's personality according to B.S Sidjabat. Third, to explain how Daniel can be a reference in forming the character of PAK teachers. The results of this research are: First, the results of interpreting the text of Daniel 6:1-29 using the Biblical Hermeneutics method with literal, grammatical, contextual, theological and historical interpretation in the form of exemplary principles of Daniel 6:1-29. Second, the results of data analysis between Law No. 14 of 2005 and the Daniel Principle of Example according to Daniel 6:1-29 which can fulfill personality competencies according to general educational standards. Third, the results of data analysis between Personality Qualities according to B.S Sidjabat and Daniel's Principle of Example according to Daniel 6:1-29 which can fulfill personality competencies according to PAK teacher education standards.